Katharine McCook Knox papers - Knox, Katharine McCook
Correspondence, index to correspondence, research material on artists and art collections, genealogical notes, clippings, printed matter, photographs, and other papers pertaining primarily to Knox's research and writing on the Sharples family of British portraitists and their work in colonial America; G.P.A. Healy, his portrait of Abraham Lincoln, and its use on a postage stamp issued on the sesquicentennial of Lincoln's birth; and the history of the "Fighting McCooks," the family of Civil War soldiers from which Knox was descended. Other subjects include social life and Republican Party activities in Washington, D.C.
Art historian. Born 1890; died 1983.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Healy, G. P. A. -- 1813-1894.; Lincoln, Abraham, -- 1809-1865 -- On postage stamps; Lincoln, Abraham, -- 1809-1865 -- Portraits; McCook family; Sharples family; Sharps family; Republican Party (U.S. : 1854- ); Art; Art -- Private collections; Art museums; Artists; Portrait painters; Portrait painting -- United States; United States -- History -- Civil War, 1861-1865.; Washington (D.C.) -- Politics and government; Washington (D.C.) -- Social life and customs; Art historians